2002
DOI: 10.1086/501980
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior Associated With Influenza Vaccination Among Healthcare Workers in Long-Term-Care Facilities

Abstract: This study identifies challenges to and opportunities for improving vaccination rates among HCWs. A message that emphasizes the health benefits of vaccination to staff members, such as including vaccination as part of a staff "wellness" program, may improve the credibility of influenza immunization programs and coverage rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 20 publications
(12 reference statements)
7
53
1
4
Order By: Relevance
“…This latter statement also does not support the extrapolation of our findings to the whole French geriatric HCW population. However, the three main reasons we found were similar to those reported in previous studies in other countries (17,19,20,23).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This latter statement also does not support the extrapolation of our findings to the whole French geriatric HCW population. However, the three main reasons we found were similar to those reported in previous studies in other countries (17,19,20,23).…”
Section: Discussionsupporting
confidence: 91%
“…However, several interpretations may attempted: i) positive correlations between occupational groups found in rehabilitation and long-term care settings, together with significantly higher vaccination rates in these settings than in acute-care ones, suggest a "group effect". It has recently been reported that a physician influences vaccination acceptance among other occupational groups in long-term care settings (23). However, it must be noted that, in the present study, the correlation between nurses and nurse assistants was higher than between physicians and other HCW (nurses and nurse assistants).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In our survey, 70.6% of GPs had received the seasonal influenza vaccine every year in the prior three years and their personal history of seasonal vaccination receipt was strongly related to their acceptability of the A/H1N1 pandemic vaccination with a significant trend towards an exposure-effect relationship. Previous studies conducted among healthcare workers showed a similar relationship between the receipt of influenza vaccine in the previous season and willingness to accept: 1) seasonal influenza vaccine in general practice [27,28], hospitals [29], and long term care facilities [30,31]; 2) pre-pandemic A/H5N1 influenza vaccines in hospitals [22,32]; and 3) A/H1N1 influenza pandemic vaccines in hospitals [22]. In addition, previous receipt of seasonal flu vaccines was associated with willingness to accept unapproved influenza-pandemic vaccination in June 2009 among the general public in the US [14].…”
Section: Resultsmentioning
confidence: 73%